Celecoxib Decreases Risk of Developing Heterotopic Ossification after Total Ankle Arthroplasty - Caroline Cristofaro BSc(Hons), MBChB; Mohammad Athar; Ellie Pinsker PhD; Bradley Meulenkamp MD, MSc, FRCSC; Timothy R. Daniels MD, FRCSC; Mansur Halai BSc (Hons), MBChB, MRCA, MRCS, FRCS (Foot & Ankle Orthopaedics)
Submission Type: Ankle Arthritis Research Type: Level 3 - Retrospective cohort study, Case-control study, Meta-analysis of Level 3 studies Introduction/Purpose: Total ankle arthroplasty (TAA) is an effective procedure for end-stage ankle arthritis. Heterotopic ossification (HO) is a common postoperative complication and can potentially have a significant impact on patient reported outcome measures (PROMs). Currently, no guidelines exist for HO prophylaxis following TAA. The aim of this study was to determine whether HO prophylaxis is associated with decreased presence and severity of radiographic HO as well as its impact on PROMs. Methods: This retrospective cohort study included all patients who underwent a primary TAA between April 2019 to May 2023 at a single academic institution. The intervention group comprised of patients prescribed 4 weeks of Celecoxib postoperatively and was compared to controls who received no HO prophylaxis. Radiographs at ≥8 months were reviewed and graded using the modified Brooker classification for severity of HO. American Orthopaedic Society Pain, Disability, Short Form Survey – 36 Physical Function, and Mental Health were assessed at follow-up. Results: One-hundred and eighty-two patients, 98 (53.8%) males and 84 (46.2%) females, were included. The mean age was 66.0±9.5 years. Ninety (49.5%) patients received HO prophylaxis and 92 (50.5%) did not. The prevalence of HO at time of follow-up was 53 (29.1%) with grade 0, 78 (42.9%) with grade 1, 22 (12.1%) with grade 2, 23 (12.6%) with grade 3, and 6 (3.3%) with grade 4. The odds of developing HO and of having increasing severity of HO were 2.30 (95% CI 1.16, 4.57) and 2.42 (95% CI, 1.38, 4.25) times greater for patients without HO prophylaxis compared to those prescribed prophylaxis (p < 0.05), respectively. There was no significant association between Celecoxib use and PROMs. Conclusion: Celecoxib for 4 weeks following primary TAA is an effective method to decrease the risk of developing HO and reducing its severity. HO has no statistically significant impact on PROMs. Celecoxib for HO prophylaxis should be considered following primary TAAs in patients who can tolerate non-steroidal anti-inflammatories.